إدارة المعرفة كمدخل للذكاء الاقتصادي - نهاد, حجاج; عبلة, خلايفة; أم الخير, بلقاسمي (University of eloued جامعة الوادي, 2020)
"الملخص: تناولنا في هذه الدراسة دور إدارة المعرفة كمدخل للذكاء الاقتصادي في المؤسسة الاقتصادية دراسة حالة عدة مؤسسات اقتصادية بالوادي وهدفنا إلى التعرف على وجهة نظر الموظفين في المؤسسات لطبيعة العلاقة بين عمليات إدارة المعرفة والذكاء الاقتصادي,ولتحقيق أهداف الدراسة استخدمنا استبانه لجمع البيانات,وقد وزعت على عينة بلغ عددها 31موظف. واعتمدنا في تحليل البيانات على التحليل الإحصائي الوصفي,المتوسطات الحسابية ,الانحرافات المعيارية ,التكرارات والنسب المئوية.وقد أفرزت نتائج التحليل الإحصائي على مجموعة من النتائج أهمها: *إدارة المعرفة هي العملية التي يتم فيها تحويل المعلومات والموارد الفكرية إلى موارد ذات قيمة عالية من أجل تطوير قابليات الأفراد والمنظمات لغرض تحقيق أهدافه؛ *الذكاء الاقتصادي هو سيرورة جمع,معالجة ونشر المعلومات بهدف تقليص حالة عدم التأكد في اتخاذ كل القرارات الاستراتيجية؛ *أسفرت نتائج اختبار العلاقة على أنه هناك علاقة ذات دلالة إحصائية بين أبعاد إدارة المعرفة وإجمالي الذكاء الاقتصادي؛ *وجود علاقة ذو دلالة إحصائية لتطبيق إدارة المعرفة على الذكاء الاقتصادي. .""   Summary :In this study, we addressed the knowledge management as an introduction to economic intelligence, studying the case study of several economic institutions in the valley , and our goal is to identify the point of view of the employees in the organization of the nature of the relationship between knowledge management and economic intelligence, and to achieve the objectives of the study .We used estha to collect data, and it was distributed to a sample of 31 employees. In the analysis of the data, we relied on descriptive statistical analysis, computational averages, standard deviation, repetitions and percentages. And the results of the statistical analysis were based on a set of results, the most important of which were: *Knowledge management is the process in which information and intellectual resources are transformed into resources of high value in order to develop the capabilities of individuals and organizations for the purpose of achieving its goals. *Economic intelligence is the process of collecting, processing and disseminating information with the aim of reducing uncertainty in all strategic decisions. *The results of the relationship test revealed that there is a statistically significant relationship between the dimensions of knowledge management and total economic intelligence. * There is a statistically significant relationship for the application of knowledge management to economic intelligence.   ."
مذكرة ماستر ادارة اعمال
Keywords: إدارة المعرفة،الذكاء الاقتصادي; Opening words: knowledge management, economic intelligence